2019
DOI: 10.1080/1331677x.2019.1679214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the employees’ engagement factors importance methodology including generation Y

Abstract: Employee engagement has a major impact on both, staff performance and overall organisation performance. Factors affecting the level of engagement vary depending on the age of the workers. These differences should be recognised by the organisation and taken into account when increasing workers' engagement. Aim of this article is to introduce a new way how to evaluate the importance of employees' engagement factors including also generation Y and provide the results of practical implementation of pilot research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Hence, it would be interesting and logical to investigate the owners and managers' perceptions of the employee turnover risk, and to determine its effect on firms, whether it has a negative effect or is neutral in case of Czech and Slovak firms. Risk sharing between personnel is an important factor of employees' engagement among the generation Y (Horváthová et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hence, it would be interesting and logical to investigate the owners and managers' perceptions of the employee turnover risk, and to determine its effect on firms, whether it has a negative effect or is neutral in case of Czech and Slovak firms. Risk sharing between personnel is an important factor of employees' engagement among the generation Y (Horváthová et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…From the position of a manager who has encountered a demanding situation and has to deal with it, but also from the point of view of the organisation in which the manager operates (Horváthová et al, 2019), the decisive factor is the choice of procedure to solve the demanding situation. Research into the ways in which the manager behaves and copes with these situations receives more attention than the characteristics, specification, and taxonomy of demanding situations (Frankovský, 2001).…”
Section: Coping With Demanding Situations In Managementmentioning
confidence: 99%
“…Literature on engagement states that employee engagement is considered as a very recent topic, where authors started to take it into consideration and talk about it widely in 2000 [27]. Several definitions were dedicated to conceptualizing the notion.…”
Section: Diversity Management and Employee's Engagementmentioning
confidence: 99%
“…[28] have mentioned that employee engagement is the degree of his/her attachment to the organization and how they identify themselves towards it. It has also been reported that employee engagement can occur when people are engaged in their work, and they are concerned and enthusiastic about their job and position and willing to put a lot of effort into it [27]. Furthermore, Kahn [29] (p. 694) who was the first one who introduced the concept, added that employee engagement can occur when "people employ and express themselves physically, cognitively, and emotionally during role performances".…”
Section: Diversity Management and Employee's Engagementmentioning
confidence: 99%